Plantas medicinais com potencial ação contra o vírus da imunodeficiência humana - Bezerra, Gustavo Silva (Universidade Federal do Tocantins, 2018)
The high prevalence of Human Immunodeficiency Virus (HIV) infection raises the importance of new and effective intervention programs in infection prevention. Adverse effects, nonadherence to treatment and, especially, HIV resistance to existing Antiretrovirals are alerts for the search for new compounds effective against this virus. Medicinal plants have proved to be a promising resource in identifying new bioactive compounds. This study is a systematic review with the purpose of performing a survey of articles available in the main electronic databases, LILACS, Medline (via PubMed), Web of Science, on medicinal plants with potential action against HIV. The search for articles for the study occurred in October 2017 and 42 articles were selected for review. Of the 42 articles selected, 51 medicinal plants that showed anti-HIV activity were evidenced, varying the mechanism of action performed, either by protease inhibitor, integrase or reverse transcriptase. There were reports of new compounds capable of improving the anti-HIV activity of antiretrovirals already marketed and 19 manuscripts presented plants with promising antiviral activity unknown. Thus, this review reinforces the need to carry out studies in order to prove the means by which the medicinal plants studied here may be the source of new drugs in the fight against human immunodeficiency virus.